Fluorosis prevalence among schoolchildren in a fluoridated community in Malaysia - Tan, B.S.; Razak, I.A.; Foo, L.C. (2005)
Objectives This study aims to assess the magnitude of the problem Of fluorosis among 10-11 year old schoolchildren in a fluoridated area in Malaysia. Methods An analytical cross-sectional design was adopted. Sampling of subjects was by a 2-stage systematic random sampling technique in Selangor, a fully fluoridated area. 1,343 10-11 year olds were assessed for fluorosis using the Dean's index. Results The prevalence of fluorosis was 58.7 (788 subjects); 478 (35.6) subjects exhibited very mild fluorosis, 196 (14.6) mild, 102 (7.6) moderate, 12 (0.9) severe and 555 (41.3) no fluorosis. Tooth prevalence was 30.1. Overall, the Community Fluorosis Index (CFI) was 0.96 and ranged from 0.23 to 1.72. Fifteen out of 30 schools had CFI > 1.0 (medium public health significance). Conclusions The prevalence of dental fluorosis in Malaysia (mostly very mild to mild) at 58.7 is indicative of slightly above optimal levels of exposure. There were pockets of areas where fluorosis were of medium public health significance (CFI > 1.0). It must be cautioned that, fluorosis if not monitored closely, can become an increasing Public health concern.